The association between subcultures and resistance to change – in a Swedish hospital clinic. Issue 4 (12th August 2014) - Carlstrom, Eric; Olsson, Lars-Eric
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the different subcultures and the employees' preparedness for change at an orthopaedic clinic in a university hospital in Sweden. Design/methodology/approach – Surveys were sent out to 179 nurses and physicians. The survey included the two instruments Organisational Values Questionnaire and resistance to change (RTC) Scale. Findings – The results suggest a dominance of a human relations culture, i.e. flexibility, cohesion and trust, in the orthopaedic clinic. These characteristics seemed to decrease RTC. Opposite to this, planning, routines and goal setting appeared to increase change-resistant behaviour. Practical implications – By predicting potential obstacles in a certain context prior to a change process, resources can be used in a more optimal way. An instrument that pinpoints the culture of a particular healthcare setting may be a useful tool in order to anticipate the possible outcome of change. Originality/value – The rational goal/internal processes dimension exerted a stronger association with RTC than in earlier studies. Deeply rooted standards and routinised care models, governed by work schedules, could be an obstacle to introducing a care model based on the individual needs of the patient. There was, however, a surprisingly low RTC. The results are contrary to the accepted understanding of public organisations known to be slow to change.